Application of Pregnancy Exercise to Improve the Quality of Sleep in Trimester III Pregnant Women in the Working Area of the Puskesmas Perumnas, Lubuklinggau City - Nadi Aprilyadi (PT FORMOSA CENDEKIA GLOBAL, 2022)
Pregnancy is a process that starts from a stage of conception until the birth of the fetus. A normal pregnancy will last 40 weeks or 9 months, Pregnancy is divided into 3 semesters, of which the first trimester lasts in 12 weeks, the second trimester is 15 weeks and the third trimester is 27 weeks. Pregnancy exercise can be useful for increasing oxygen circulation to muscles and body tissues, as well as improving blood circulation, so it can reduce the physical discomfort and reduce complaints of pregnant women. It is known that the quality of sleep in pregnant women increases by implementing pregnancy exercise in the working area of ​​the Perumnas Public Health Center. This research is descriptive using a case study approach. The subjects in this study were 2 mothers with of third trimester pregnancy. This was carried out directly with an initial assessment of patients with sleep disorders and then intervention by giving the pregnant exercise to improve sleep quality. After the application of pregnancy exercise can improve the quality of sleep in pregnant women in the third trimester.